Strategi Optimalisasi Media Sosial Untuk Meningkatkan Performa Pemasaran UMKM: Studi Kasus pada Lapak Kirani Kota Bima - Ita Purnama; Nufus Al Maidah; Indah Syari (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in national economic growth. In today’s digital era, leveraging technology—particularly social media—has become an essential marketing strategy to ensure business sustainability. Lapak Kirani, a culinary MSME located in Bima City, has faced challenges in optimizing social media as a promotional tool. This community service program aimed to assist Lapak Kirani in independently managing digital marketing by providing training on social media account creation, promotional content development, and effective caption writing. The implementation method consisted of four stages: observation, socialization, mentoring, and evaluation. The results indicated an improvement in the MSME owner's understanding and skills in executing digital marketing strategies. This assistance is expected to expand product marketing reach and enhance the competitiveness of MSMEs in a sustainable manner.